The effect of isophorone diisocyanate-polyhydroxyl groups modified water hyacinth fibers (Eichhornia crassiper) on properties of low density polyethylene/acrylonitrile butadiene styrene (LDPE/ABS) composites - Supri, A. Ghani, Dr.; Ismail, H. (Taylor & Francis Group, LLC., 2011)
Link to publisher's homepage at http://www.taylorandfrancisgroup.com/